The Absence of Caspase-8 in the Dopaminergic System Leads to Mild Autism-like Behavior - Suárez-Pereira, I.; García-Domínguez, I.; Bravo, L.; Santiago, M.; García-Revilla, J.; Espinosa-Oliva, A. M.; Alonso-Bellido, I. M.; López-Martín, C.; Pérez-Villegas, E. M.; Armengol, J. A.; Berrocoso, E.; Venero, J. L.; et al. (Frontiers in Cell and Developmental Biology, 2022)
Apoptotic caspases are believed to play critical roles in the elimination of excessive and nonfunctional synapses and the removal of extra cells during early developmental stages. Therefore, an impairment of this process may be the basis for numerous neurological and psychiatric diseases. This view is especially relevant for dopamine due to its pleiotropic roles in motor control, motivation, and reward processing. Here, we have analyzed the effect of caspase-8 (CASP8) deletion on catecholaminergic neurons development and performed a wide range of neurochemical, ultrastructural, and behavioral assays. To achieve this, we performed selective deletion of the CASP8 gene in cells expressing tyrosine hydroxylase (TH) using Cre-loxP-mediated recombination. Stereological analysis demonstrated an increase in the number of TH+ neurons in the substantia nigra. In the striatum, basal extracellular levels and potassium-evoked DA release were significantly reduced in mice lacking CASP8, a clear indication of dopaminergic hypofunction in dopaminergic innervating tissues. This view was sustained by analysis of the synapsis in the striatum using electron microscopy. Interestingly, at the behavioral level, CASP8-deficient mice exhibited alterations reminiscent of autism spectrum disorder (ASD). Our study revitalizes the potential involvement of dopaminergic transmission in ASD and provides a mild model to gain more information on the pathogenesis of ASD.